Nanoformulations of quercetin: a potential phytochemical for the treatment of uv radiation induced skin damages - Nancy Tripathi; Surajpal Verma; Manish Vyas; Narendra Singh Yadav; Subhajit Gain; Gopal Lal Khatik (Brazilian Journal of Pharmaceutical Sciences, 2022)
Abstract The continuous prolonged exposures of sun light especially the ultra violet (UV) radiation present in it, cause not only the risk of skin cancer but also it may cause premature skin aging, photodermatoses and actinic keratoses. Flavonoids (including Flavane, Flavanone, Flavone, Flavonol, Isoflavone, Neoflavone etc.) having potent antioxidant activity, used as topical applications for protection against UV induced skin damages as well as for skin care. Most commonly used flavonoid is quercetin (Flavonol), which is present in fruits, vegetables, and herbs. We aim to review the research focused on development of different novel formulations to treat UV radiations induced skin diseases. In this review, several formulations of flavonoid quercetin were discussed and their outcomes were compiled and compared in context to solubility, stability and efficiency of application. On the basis this comparative analysis we have concluded that three formulations, namely glycerosomes, nanostructured lipid carriers and deformable liposomes hold good applications for future aspects for topical delivery of quercetin. These formulations showed enhanced stability, increased quercetin accumulation in different skin layers, facilitated drug permeation in skin and long-lasting drug release.